1979
DOI: 10.1136/gut.20.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum proteins during attacks of ulcerative colitis as a guide to patient management.

Abstract: SUMMARY Serial measurements of 11 serum proteins have been made throughout 39 admissions of 36 patients to hospital for the treatment of acute attacks of ulcerative colitis. There was a striking correlation between rapid changes in C-reactive protein and pre-albumin concentrations and the clinical response to medical treatment. Measurements of the a,-acid glycoprotein, albumin, and total serum protein concentrations at the time of admission were found to correlate with the outcome of the attack. Measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 17 publications
(12 reference statements)
4
29
1
Order By: Relevance
“…The main aim of this study, however, was not to define the prevalence of protein abnormalities, but to determine whether protein levels changed appropriately with tumour growth during follow-up and could be of value as tumour markers to predict recurrence. During follow-up no overall rise in the concentration of any protein was found, despite clinical or radiological appearance of tumour; nor did we find falls in pre-albumin levels, reported to give information complementary to CRP in other diseases (Buckell et al, 1979). Levels above the normal range did not rise consistently either from 3 months after operation or from 3 months before recurrence up to the time of recurrence, suggesting that factors other than tumour load are also important in determining the concentrations of these proteins.…”
mentioning
confidence: 51%
“…The main aim of this study, however, was not to define the prevalence of protein abnormalities, but to determine whether protein levels changed appropriately with tumour growth during follow-up and could be of value as tumour markers to predict recurrence. During follow-up no overall rise in the concentration of any protein was found, despite clinical or radiological appearance of tumour; nor did we find falls in pre-albumin levels, reported to give information complementary to CRP in other diseases (Buckell et al, 1979). Levels above the normal range did not rise consistently either from 3 months after operation or from 3 months before recurrence up to the time of recurrence, suggesting that factors other than tumour load are also important in determining the concentrations of these proteins.…”
mentioning
confidence: 51%
“…7,26 Other studies have pointed to the signi®cance of a persistently elevated or rising C-reactive protein (CRP) as a predictor of the need for surgery. 27 First attacks and extensive disease are suggested to be associated with a poor response to medical treatment. 28 A rising arterial pH may signify pending toxic megacolon.…”
Section: Factors Predicting Outcomementioning
confidence: 99%
“…The prognostic value of serum albumin, prealbumin and C-reactive protein estimation was shown by Buckell et al (1979) who emphasized the (Brooke, 1968;Norland and Kirsner, 1969;Jalan et al, 1969;Goligher et al, 1970;Binder, Patterson and Gloyzer, 1974). The usual advice is for surgery within 72 hr, and there is extreme urgency if plain X-rays reveal gas-filled undermined ulcers and mucosal islands (Brooke, 1968) (Fig.…”
Section: Preventionmentioning
confidence: 99%
“…Sirinek et al (1977) With regard to the type of operation, good results have been reported using the Turnbull procedure of loop ileostomy and venting colostomy (Shipp, 1974;Fazio, Turnbull and Goldsmith, 1976), but this necessitates a secondary colectomy, whereas with immediate colectomy increasingly low mortality rates have been achieved (Binder et al, 1974;Strauss et al, 1976;Sirinek et al, 1977). The case for immediate rectal excision is controversial.…”
Section: Preventionmentioning
confidence: 99%